2019
DOI: 10.31234/osf.io/k5xhg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thriving at Work: A Meta-Analysis

Abstract: Summary Thriving at work refers to a positive psychological state characterized by a joint sense of vitality and learning. On the basis of Spreitzer and colleagues' model, we present a comprehensive meta‐analysis of antecedents and outcomes of thriving at work (K = 73 independent samples, N = 21,739 employees). Results showed that thriving at work is associated with individual characteristics, such as psychological capital (rc = .47), proactive personality (rc = .58), positive affect (rc = .52), and work engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The positive indirect effects of experienced service‐oriented HPWS on the two outcomes through thriving at work and the serial mediation of thriving at work and psychological health on the experienced service‐oriented HPWS–service performance relationship reinforces the notion of mutuality in the employment relationship. Furthermore, the serial mediation that shows psychological health to be more proximal to service performance relative to thriving at work accounts for the documented influence of thriving at work on performance (Kleine et al, ; Porath et al, ). Contrary to our prediction, unit service leadership only indirectly influenced service performance but not psychological health through thriving at work.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The positive indirect effects of experienced service‐oriented HPWS on the two outcomes through thriving at work and the serial mediation of thriving at work and psychological health on the experienced service‐oriented HPWS–service performance relationship reinforces the notion of mutuality in the employment relationship. Furthermore, the serial mediation that shows psychological health to be more proximal to service performance relative to thriving at work accounts for the documented influence of thriving at work on performance (Kleine et al, ; Porath et al, ). Contrary to our prediction, unit service leadership only indirectly influenced service performance but not psychological health through thriving at work.…”
Section: Discussionmentioning
confidence: 99%
“…Carmeli & Spreitzer, ). Previous research reported thriving at work to relate to employee job performance (Kleine et al, ; Paterson et al, ; Porath et al, ; Wallace, Butts, Johnson, Stevens, & Smith, ). The preceding discussion that (a) experienced service‐oriented HPWS relates to thriving at work and (b) thriving at work promotes employee work outcomes suggests the following hypotheses.Hypothesis Thriving at work positively relates to psychological health and mediates the experienced service‐oriented HPWS–psychological health relationship.Hypothesis Thriving at work positively relates to service performance and mediates the experienced service‐oriented HPWS–service performance relationship.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations